"Teaching is so WEIRD". (8th June 2015) - Lancy, David F.
Abstract: Direct active teaching by parents is largely absent in children's lives until the rise of WEIRD (Western, educated, industrialized rich, democratic) society. However, as mothers become schooled and missionized – like Kline's Fijian subjects – they adopt "modern" parenting practices, including teaching. There is great variability, even within WEIRD society, of parental teaching, suggesting that teaching itself must be culturally transmitted.